Semiotics as a Theory of Representation - Searle, John R. (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Much of semantic theory is based on the mistake of supposing that the primary units of meaning are individual expressions such as words, symbols, and signs. On the contrary, the proper units of analysis have to be whole sentences or propositions. The individual word only functions as it contributes to the meaning of the sentence (it may be a one word sentence), because only the sentence can give us truth conditions or other conditions of satisfaction. This is an old point in semantic theory, but its implications are not always properly understood, and the aim of this paper is to explore some of those implications. Keywords: Speech acts; Drawings; Semiotics; Proposition; Semantic phenomena.